2019
DOI: 10.1159/000504334
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Standardization in Commercial Thickeners Used in the Management of Dysphagia

Abstract: Introduction: Oral feeding safety is necessary to provide nutrition, hydration, and eating pleasure for patients with dysphagia. Commercial thickeners are prescribed for these patients to change food viscosity and may alter the proper preparation of modified food. Objective: Analyze composition, employed terminology, preparation instructions, recommended amount and weight of provided measuring spoons, nutritional information, and viscosity of 7 commercial thickeners. Methods: The sample comprised all thickener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…In contrast, for apple juice samples thickened with guar gum, the syringe flow test resulted in a level escalation from “mildly thick” to “moderately thick over a 3-month period. These changes are in line with the assessment of consistency differences between the methodologies (viscometer and flow) stipulated by NDD and IDDSI, as highlighted in the study conducted by Machado et al [ 26 ]. They conducted an investigation where they utilized seven commercial thickeners to create products, subsequently subjecting them to both viscosity analysis using a viscometer and the IDDSI flow test.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, for apple juice samples thickened with guar gum, the syringe flow test resulted in a level escalation from “mildly thick” to “moderately thick over a 3-month period. These changes are in line with the assessment of consistency differences between the methodologies (viscometer and flow) stipulated by NDD and IDDSI, as highlighted in the study conducted by Machado et al [ 26 ]. They conducted an investigation where they utilized seven commercial thickeners to create products, subsequently subjecting them to both viscosity analysis using a viscometer and the IDDSI flow test.…”
Section: Discussionsupporting
confidence: 82%
“…This has been verified using a swallowing model by Stading et al [7]. In addition, previous reports have also indicated that coherence and consistency of a food bolus can help to increase tactile sensitivity along the swallowing pathway and thus promote a safe swallow [8,9].…”
Section: Introductionmentioning
confidence: 67%
“…Nondysphagic people perceived sensory differences in fluids of the same IDDSI level. By contrast, the same AV generates different IDDSI levels, and the same level is associated with different apparent viscosities (Machado et al., 2019). These differences result in risk for people with dysphagia.…”
Section: Resultsmentioning
confidence: 99%